2013
DOI: 10.4028/www.scientific.net/amm.295-298.2254
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Idling Stops on Red Light at Signalized Intersection under Random Arrival

Abstract: Aiming at the issues of global warming and climate change, this research proposed three kinds of models to evaluate the effect of idling stops, expressed as the idling stop time, on red light at signalized intersection under random arrival of vehicles. The first one evaluates the maximum idling stop time, whereas the second one focuses on the idling stop time conditioned by an acceptable remaining red time. The third one is then used to estimate the increment of the idling stop time as the driver’s willingness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Accordingly, Martin et al (2017) highlighted that it is generally better to turn off and restart the vehicle, even for short stops for emission reduction, and Omar et al (2020) found that vehicle positioning in a queue and congestion levels significantly impact the decision to turn off the engine in India [5,15]. Wu et al (2015) indicated that the idling stop policy has significant potential savings in CO 2 emissions from a case study in Taipei City [16]. (2016) underscored the importance of adopting idle-reduction strategies to mitigate the adverse effects of vehicle idling on air quality at signalized intersections in urban areas and suggested multiple mitigation measures, such as auxiliary power units (APUs), direct-fired heaters, fuel cells, truck stop electrification, improving signal timing, promoting public transport, implementing land use and transport policies, encouraging non-motorized transport modes, and so forth [17][18][19][20].…”
Section: Environmental Effect Of Vehicle Idlingmentioning
confidence: 99%
“…Accordingly, Martin et al (2017) highlighted that it is generally better to turn off and restart the vehicle, even for short stops for emission reduction, and Omar et al (2020) found that vehicle positioning in a queue and congestion levels significantly impact the decision to turn off the engine in India [5,15]. Wu et al (2015) indicated that the idling stop policy has significant potential savings in CO 2 emissions from a case study in Taipei City [16]. (2016) underscored the importance of adopting idle-reduction strategies to mitigate the adverse effects of vehicle idling on air quality at signalized intersections in urban areas and suggested multiple mitigation measures, such as auxiliary power units (APUs), direct-fired heaters, fuel cells, truck stop electrification, improving signal timing, promoting public transport, implementing land use and transport policies, encouraging non-motorized transport modes, and so forth [17][18][19][20].…”
Section: Environmental Effect Of Vehicle Idlingmentioning
confidence: 99%